Mediastinal Pancreatic Pseudocysts - Krzysztof Dąbkowski; Andrzej Białek; Maciej Kukla; Janusz Wójcik; Andrzej Smereczyński; Katarzyna Kołaczyk; Tomasz Grodzki; Teresa Starzyńska (Korean Society of Gastrointestinal Endoscopy, 2017)
Mediastinal pseudocysts are a rare complication of acute pancreatitis. Lack of uniform treatment standards makes the management of this condition a clinical challenge. We report the case of a 43-year-old patient who presented with a left pleural effusion. Pleural fluid revealed a high amylase concentration consistent with a pancreaticopleural fistula. Endoscopic retrograde cholangiopancreatography (ERCP) revealed a disruption of the pancreatic duct with free outflow of contrast medium into the thoracic cavity. A pancreatic stent was placed. The second day after the ERCP, the patient developed septic shock and was admitted to the intensive care unit. Computed tomography (CT) revealed mediastinal pseudocysts and bilateral pleural effusions. After bilateral drainage of the pleural cavities, the patient improved clinically, and a follow-up CT scan showed that the fluid collection and pseudocysts had resolved. We discuss the optimal strategies for diagnosing and treating patients with pancreatic thoracic pseudocysts and fistulas, as well as review the management of these conditions.